Prospects for EU Finance after the British Withwdrawal from the European Union - Stabryła-Chudzio, Katarzyna (Studia Oeconomica Posnaniensia, 2018)
As a result of the referendum held on 23 June 2016 in the UK, a majority of citizens voted in favour of the withdrawal of their country from the EU structures. It should be emphasized that this is not synonymous with the immediate resignation of membership by Great Britain until the start of the procedure with the European Union institutions. However, this event should become a pretext for a clearer than ever question about the future of the European Union. Because of a multithreading topic, the aim of this article will be an attempt to outline the scenario for new financial perspectives, as it may change the EU budget. Calculations of EU revenue relating to the twenty-seven states will be presented, together with the change in the contributions of the British and correction mechanism to the UK.